Laypersons' perception of smile esthetics from different backgrounds - Fereshteh Najarzadegan; Faezeh Eslamipour (Wolters Kluwer Medknow Publications, 2024)
Background: Smile esthetics can be subjective. This study aims to assess the effect of culture/geographic location on judging smile esthetics by comparing the perception of smile characteristics between American laypersons (Western culture) and Iranians (Eastern). Materials and Methods: One hundred residents from each country were recruited for this analytical cross-sectional study. A frontal picture of a posed smile with standard norms which are mentioned in the Contemporary Orthodontics textbook by William R. Proffit was selected. Adobe Photoshop 7 was used to alter midline diastema, gingival display (GD), maxillary midline-to-face discrepancy, buccal corridor (BC), and smile arc. Images were given to groups to determine the most attractive and acceptable smile. Data were analyzed by Chi-square, Mann-Whitney, and Spearman correlation coefficient in SPSS-22 (α =0.05). Results: Americans were less critical in judging diastema (P < 0.001), GD (P = 0.013), and BC (P = 0.004) for smile attractiveness than Iranians. No difference was between the two groups in choosing the acceptability threshold and determining the most attractive smile except for BC (P = 0.002). Conclusion: Overall, Americans were more tolerant of variations in smile characteristics than Iranians. Both groups agreed on most smiles. Therefore, it seems that it is reasonable to use similar standards for smile characteristics while considering the small differences.